Forensic geotechnical engineering - V.V.S. Rao; G.L. Sivakumar Babu (Developments in geotechnical engineering (Springer (Firm)), 2016)
In this edited volume on advances in forensic geotechnical engineering, a number of technical contributions by experts and professionals in this area are included.